Viabilidade econômica da produção de hortaliças orgânicas em média escala: estudo de caso na região metropolitana de Sorocaba-SP - Garcia, Éllen da Silva (2020)
Organic production is recent in Brazil, starting in the 1970s, at a time when conventional production already had several credit incentives and was expanding. Brazilian agriculture has great representativeness in the world trade and, every year, the organic market conquers new consumers and has been increasing its revenue, generating more demand for production. The objective of this work was to evaluate the difficulties and potential of organic agriculture in Brazil and to carry out an economic feasibility analysis in an organic vegetable production in the metropolitan region of Sorocaba, SP. To achieve the first objective, a bibliographic review on organic agriculture was carried out in databases of scientific journals, through searches for keywords that make up the study area. As difficulties, we highlight the inadequate infrastructure and lack of knowledge about organic cultivation. The characteristics of organic production, such as multiproduction, generate difficulties in the elaboration of financial and economic projects and shortages of labor in the field and lower yields in the production of vegetables, compared to conventional ones. The issues that promote organic agriculture are the growth of consumption, the existence of certification, Public Policies and scientific research that promote the modernization of practices in organic agriculture, improving efficiency in production. The economics analysis was based on an annual cash flow for the case study, from which the economic indices Net Present Value (NPV), Internal Rate of Return (IRR), and Simple and Discounted Payback. A five-year planning horizon was considered. Sensitivity analysis was also carried out for commercialization values and yield rates of vegetables. It was observed that the project was economically unfeasible when considering the cost of land acquisition as an initial investment. However, it was feasible if conducted through land rent. In this scenario, there are vegetables that, depending on the sale prices and (or) the income values, can make the enterprise economically unfeasible. With the simulation of an increase in the yield rate of vegetables, alone or in combination, the project was less sensitive to the variation in selling prices. In addition, the increase in yield rate would increase the NPV value by 163.48%, the IRR by 22% and the Cost Benefit Ratio by 10% and reduce the return on investment value by almost one year. It is concluded with this work that the economic viability of the production of organic vegetables on a medium scale depends on the initial investment, especially in the acquisition of land, the type of vegetables produced and the yield rate for commercialization.